Patients’ and Caretakers’ Satisfaction at Western Regional Hospital, Pokhara, Nepal - Dahal, Sushma; Bhandari, Ram Prasad (Dhaulagiri Journal of Sociology and Anthropology, 2012)
Curative services are highly demanded component of health service. Besides competence in technical aspects; behavior of health care providers, availability of consumer friendly environment and the trusting relationship with the physician along with open two way communication between health care provider and consumer determines the consumers’ perception about the quality of service that further determines whether they seek and continue to use services. This study was conducted with the objective of finding out consumers’ satisfaction with the services of Western Regional Hospital, Pokhara and the findings can be helpful in designing interventions accordingly. A client-exit interview was conducted which included 146 respondents representing both old and new OPD cases of the hospital. Two Focus Group Discussions were also conducted. Results obtained showed that service of hospital were of good satisfaction to more than half of the respondents. Drug availability and cheap cost of service were strong aspects of hospital. More than half of the respondents had visited private medicals before coming to hospital. Poor place of examination, poor hospital sanitation, long waiting time for doctor and service of staffs other than doctor were some of the aspects that consumers were poorly satisfied with. Fifty four out of 115 (47%) who had spent less than 5 minutes with the doctor, had good satisfaction with doctors’ service. Hence, consumers’ satisfaction is influenced by the factors like behavior of attending physician and other hospital staffs, place of examination, waiting time for doctor, hospital sanitation etc. DOI: http://dx.doi.org/10.3126/dsaj.v5i0.6364 Dhaulagiri Journal of Sociology and Anthropology Vol. 5, 2011: 205-16